THE IMPACT OF THE INDUSTRIAL PROCESSING ACTIVITY OF THE OIL AT S.C. ARPECHIM ON THE AIR QUALITY - Emilia POPESCU, Marian POPESCU, Mihai Lucian MĂNOIU; Emilia POPESCU, Marian POPESCU, Mihai Lucian MĂNOIU; Emilia POPESCU, Marian POPESCU, Mihai Lucian MĂNOIU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2012)
The atmospheric air is the main component of the surrounding environment directly involved in the pollution phenomenon. Together with the other sequences of the biosphere it represents a prior element for maintaining life, for keeping its natural quality, representing a major objective for human communities. As Barde I. Ph., Economie et Politique de l’environment, P.V.F. Paris 1992 showed, we can talk about air pollution when the presence of a foreign substance from its normal composition, or the variation of its natural components, in important proportions, are susceptible to determine a harmful effect or to create a prejudice or discomfort. The European Council environmental protection Committee stated even since 1967 that a normal constituent of the air must be considered pollutant when its concentration exceeds the normal background with 0, 03%. The purpose of the present work is to analyze the pollution degree of the environment (air) generated by S.C. ARPECHIM in the areas of Pitesti – Environment protection agency, Pitesti – Stadium, Pitesti – Prundu neighborhood, Bradu, Oarja, Topoloveni, Stefanesti – Valea Mare.